DNA Sequence Analysis of rdxA and frxA from 12 Pairs of Metronidazole-Sensitive and -Resistant Clinical Helicobacter pylori Isolates - Kwon, D. H. (American Society for Microbiology, 2001)
We previously reported that inactivation of rdxA and/or frxA converted Helicobacter pylori from metronidazole sensitive to metronidazole resistant. To examine the individual roles of rdxA and frxA in the development of metronidazole resistance in H. pylori, we examined the status of rdxA and frxA from 12 pairs of metronidazole-sensitive and -resistant H. pylori isolates obtained following unsuccessful therapy containing metronidazole. Arbitrary primed fingerprinting analyses revealed that the genotypes of 11 sensitive and resistant pairs of strains were essentially identical. Amino acid sequence identities of RdxA and FrxA from the 14 metronidazole-sensitive isolates ranged from 92 to 98% and 95 to 98%, respectively, compared to that of H. pylori J99 (MIC, 1 μg/ml). All strains with high-level metronidazole resistance (MICs, 128 μg/ml) contained premature truncation of both RdxA and FrxA caused by nonsense and/or frameshift mutations. Strains with intermediate resistance to metronidazole (MICs, 32 to 64 μg/ml) contained a single premature truncation and/or altered RdxA and FrxA caused by nonsense, frameshift, and unique missense mutations. The low-level metronidazole-resistant strains (MICs, 8 μg/ml) contained unique missense mutations in FrxA but no specific changes in RdxA. The results demonstrate that alterations in both the rdxA and frxA genes are required for moderate and high-level metronidazole resistance and that metronidazole resistance that develops during anti-H. pylori therapy containing metronidazole is most likely to involve a single sensitive strain infection rather than a coinfection with a metronidazole-resistant strain.